A theology of Mark's Gospel : good news about Jesus the Messiah, the Son of God - Garland, David E.; d (Grand Rapids, MI : Zondervan, 2015)
Theology of Mark's Gospel is the fourth volume in the BTNT series. This landmark textbook, written by leading New Testament scholar David E. Garland, thoroughly explores the theology of Mark's Gospel. It both covers major Markan themes and also sets forth the distinctive contribution of Mark to the New Testament and the canon of Scripture, providing readers with an in-depth and holistic grasp of Markan theology in the larger context of the Bible. This substantive, evangelical treatment of Markan theology makes an ideal college- or seminary-level text.--Publisher.
The Orientation of This Study and the Historical Framework for Mark's Theology -- A Literary and Theological Reading of Mark's Gospel -- The Introduction to the Gospel and to Jesus as the Messiah and Son of God (Mark 1:1-13) -- Christological Titles in Mark -- Enacted Christology in Mark -- The Presentation of God in the Gospel of Mark -- The Kingdom of God in Mark -- The Secrecy Motifs in Mark -- Mark's Theology of Discipleship -- The Requirements, Costs, and Rewards of Discipleship -- Mission in Mark -- Mark's Theology of Atonement and Salvation -- Mark's Eschatology -- The Ending of Mark's Gospel: A New Beginning.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Divinity -- Biblical teaching; Jesus Christ -- Person and offices -- Biblical teaching; Jesus Christ - Person and offices - Biblical teaching; Jesus Christ - Divinity - Biblical Teaching; Bible. Mark - Theology